Comments on a study of the social validity of the developmental disability parent training program Stepping Stones Triple P - Mazzucchelli, Trevor; Studman, L.; Whittingham, K.; Sofronoff, K. (CITTÁ APERTA EDIZIONI, 2010)
Probst, Glen, Spreitz, and Jung (2010) described an evaluation of the social validity of the parenting intervention Stepping Stones Triple P (SSTP). In this evaluation, 33 masters-level psychology students viewed one of the program resources and rated the strategies of quiet time and time out as lacking in both ethical acceptability and practical applicability. On the basis of this, the authors recommended revisions to the content of SSTP. The present paper provides additional information about SSTP to correct possible misconceptions, and provide further comments on Probst and colleagues’ (2010) findings. SSTP has been demonstrated to be effective with a range of parents of children with diverse developmental disabilities and there is considerable support for the validity and effectiveness of the specific elements in question. Given this, it is argued that while there will inevitably be variations in how individuals accept program content, rather than altering program, it may be more appropriate to address those variables related to the acceptability of content. To this end, it is suggested that future research could usefully investigate influences on perceptions of content and, in particular, practical strategies to overcome barriers to the acceptance of socially valid and empirically supported methods.